Indonesian Science Teachers' Perspectives on the Integration of Critical Thinking in Science Learning: Instrument Adaptation and Validation - Salma Hafizhati Millatina Azka; Siti Fathonah; Wati Istanti; Prasetyo Listiaji (Universitas Syiah Kuala, 2026)
The gap between teachers' efforts and students' weak critical-thinking performance underscores the need to map teachers' perspectives and internal barriers by providing evaluation instruments that can assess them validly and empirically. This study aimed to validate an adapted instrument to measure science teachers' perspectives on critical thinking integration (CTI) and examine the role of gender and teaching experience on these perspectives. A cross-sectional survey was conducted with 47 science teachers in Central Java, Indonesia. Data were analyzed using confirmatory factor analysis (CFA) for construct validity, Cronbach's alpha for reliability, the Mann-Whitney U test for gender differences, and linear regression for the effect of teaching experience. The CFA and reliability analyses confirmed a valid and reliable six-item unidimensional model (RMSEA = 0.074; CFI = 0.966; TLI 0.944; a = .784). Descriptive analysis indicated that teachers had a strong professional commitment and conceptual understanding of CTI, but perceived students' critical thinking skills as suboptimal. Statistical tests revealed no significant differences in perspectives based on gender. Similarly, teaching experience did not significantly predict teachers' perspectives, although a positive trend was found in optimism about students' critical thinking potential among experienced teachers. These findings suggest professional convergence among Indonesian science teachers, where perspectives are shaped more by universal pedagogical frameworks than by demographic factors. Professional development programs should be designed universally, with a focus on practical instructional strategies to bridge the gap between teacher beliefs and students' critical thinking